Industrial, Collaborative and Mobile Robotics in Latin America: Review of Mechatronic Technologies for Advanced Automation - Jose Cornejo; S. Barrera; C. A. Herrera Ruiz; F. Gutierrez; M. O. Casasnovas; Leonardo Kot; M. A. Solis; R. Larenas; F. Castro-Nieny; M. R. Arbulú Saavedra; R. Rodríguez Serrezuela; Y. Muñoz Londoño; Alejandro Serna; D. Ortega-Aranda; S. Aranda-Miramontes; I. Chang; M. Cardona; A. Carrasquilla-Batista; R. Palomares; R. Rodriguez; Ruben Parisuaña; Miguel Bórquez; Oscar Navarro; Fernando Sanchez; I. A. Bonev; Jonathan Coulombe; F. Martín Rico; B. L. Treviño-Elizondo; H. García-Reyes; A. Sollazzo; A. Dubor; A. Markopoulou; C. De Marinis; Marco Chacin; Andres Mora; M. Pérez-Ruiz; A. Ribeiro; E. A. L'Huillier (Emerging Science Journal, 2023)
Mechatronics and Robotics (MaR) have recently gained importance in product development and manufacturing settings and applications. Therefore, the Center for Space Emerging Technologies (C-SET) has managed an international multi-disciplinary study to present, historically, the first Latin American general review of industrial, collaborative, and mobile robotics, with the support of North American and European researchers and institutions. The methodology is developed by considering literature extracted from Scopus, Web of Science, and Aerospace Research Central and adding reports written by companies and government organizations. This describes the state-of-the-art of MaR until the year 2023 in the 3 Sub-Regions: North America, Central America, and South America, having achieved important results related to the academy, industry, government, and entrepreneurship; thus, the statistics shown in this manuscript are unique. Also, this article explores the potential for further work and advantages described by robotic companies such as ABB, KUKA, and Mecademic and the use of the Robot Operating System (ROS) in order to promote research, development, and innovation. In addition, the integration with industry 4.0 and digital manufacturing, architecture and construction, aerospace, smart agriculture, artificial intelligence, and computational social science (human-robot interaction) is analyzed to show the promising features of these growing tech areas, considering the improvements to increase production, manufacturing, and education in the Region. Finally, regarding the information presented, Latin America is considered an important location for investments to increase production and product development, taking into account the further proposal for the creation of the LATAM Consortium for Advanced Robotics and Mechatronics, which could support and work on roboethics and education/R+D+I law and regulations in the Region. Doi: 10.28991/ESJ-2023-07-04-025 Full Text: PDF